Myanmar Agricultural Performance Survey (MAPS), Round 5 - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The Myanmar Agricultural Performance Survey (MAPS) is a nationwide phone panel consisting of approximately 4,663 households. The objective of the survey is to collect data on farm characteristics and agricultural assets, area and crops planted, access to inputs, crop marketing, and constraints in agricultural activities. The respondents interviewed are a sub-sample of the Myanmar Household Welfare Survey. A novel sampling strategy in combination with the development of household and population weights allows for estimates that are nationally, regionally, and urban/rural representative. MAPS Round 5 survey was implemented by phone by Myanmar Survey Research (MSR) from January to March, 2024. The MAPS collected information on household characteristics, overall area cultivated, crops grown, security problems, input use and farm management practices, yields, sales, output prices, and marketing behavior. MAPS Round 5 focused on the agricultural activities of crop farmers during the monsoon of 2023.